Epidemiology and ecology of type 1 diabetes mellitus in children and adolescents of Krasnodar Region - Irina Yur'evna Chernyak; Viktoriya Alekseevna Shashel' (Сахарный диабет)
Aims. to investigate the influence of environmental pollution on epidemiology of type 1 diabetes mellitus (T1DM) in children and adolescents of Krasnodar Region. Materials and Methos. Epidemiologic study was based on regional T1DM register data and official reports by medical facilities (form #112). Environmental survey was conducted according to the method of Shashel et al. Results. Epidemiologic study revealed increasing prevalence of T1DM among children and adolescents of Krasnodar Region for the period from 2000 to 2012 yy. Average prevalence of T1DM was estimated at 68.08 (children) and 135.78 (adolescents), and incidence at 10.08 and 17.01 per 100 000 inhabitants, respectively. Epidemiologic trend quantitatively correlates with ecological disturbance in resident areas of the population in question. Areas recognized as adverse environment reported a 2.8?3.2-fold increase in T1DM appealability as measured against neighboring areas with favourable ecologic environment.  Conclusion. Higher levels of environmental pollution drive both incidence and prevalence of T1DM in children and adolescents of Krasnodar Region, plausibly through induction of autoimmune process in the pancreas.